(untitled) (Journal of Philosophy Culture and Political Science, 2024)
This paper investigates the burgeoning field of Turkic language education in South Korea, highlighting its historical context, current landscape, and future prospects. As globalization and South Korea’s engagement with resource-rich Central Asia intensify, the significance of Turkic languages in fostering cultural understanding and promoting multiculturalism within Korea has become evident. This article explores the current landscape of Central Asian and Turkic language education in South Korea, focusing specifically on Kazakh language education. By analyzing existing programs, challenges faced by educators and learners, and potential areas for growth, this research aims to contribute to a deeper understanding of this developing field and its significance for Korea’s expanding soft power and cross-cultural diplomacy efforts. Despite the growing interest in Turkic language education, several obstacles hinder its expansion, including limited resources and the perceived difficulty of Turkic languages. To address these challenges, collaborations with Turkic-speaking countries are proposed, along with establishing a Central Asian cultural center in South Korea as a strategic move to promote Turkic language education, enhance cultural exchange, and strengthen Korea’s relationships with Central Asian nations. Such initiatives would foster reciprocity in cultural exchange, promote soft power for Kazakhstan, support Turkic language learning, and enhance Korea’s relations with Central Asian nations. While challenges exist, the prospects for Turkic language education in South Korea are promising. Key words: Turkic languages, South Korea, Kazakh language, Central Asia, multiculturalism, Kazakhstan, soft power diplomacy, culture centers, cross-cultural exchange, globalization